Quantitative evaluation of modified advanced platelet-rich fibrin buffy coat among diabetic patients and tobacco smokers with chronic periodontitis - Neelam Das; B J Janardhana Amaranath (Wolters Kluwer Medknow Publications, 2022)
Background: The use of biofuel like platelet-rich fibrin (PRF) may enhance the healing potential of the tissues in tobacco smokers and diabetic patients. Aim: To evaluate the modified advanced PRF (A-PRF) buffy coat quantitatively in uncontrolled type-2 diabetic patients and tobacco smokers with chronic periodontitis by determining the size outcome of the buffy coat, the platelet and leukocyte concentration, and also to find out the influence of gender on these parameters. Materials and Methods: In this cross-sectional study, 180 generalized chronic periodontitis patients (46-55 years) were enrolled, Group 1 (Control group): 60 systemically healthy subjects; Group 2 (Test group): 60 Heavy tobacco smokers; and Group 3 (Test group): 60 uncontrolled type 2 diabetic patients. 15 ml of blood was drawn from all subjects to assess the size outcome, platelet, and leukocyte concentration also to find out the influence of gender on the various parameters of the prepared modified (A-PRF) membrane. Results: Uncontrolled type-2 diabetic patients had maximum height (23.39 ± 1.69 mm) and width (7.26 ± 0.16 mm) of modified (A-PRF) clot when compared to healthy individuals and tobacco smokers. The total number of platelet (245.38 ± 40.72 1000/ul) and leukocyte count (6.11 ± 0.60 1000/ul) and their percentage of concentration were 95.21 ± 2.16% and 77.25% ±1.98%, respectively, and is significantly higher in uncontrolled type-2 diabetic patients (P ≤ 0.05). Females were associated with the larger sized modified (A-PRF) clot with more number of platelets and leukocytes count than males. Conclusions: Size outcome of modified (A-PRF) clot was found to be comparatively larger in uncontrolled type-2 diabetic patients particularly in females of all the groups when compared to males. Among the hematological parameters, the total count as well as the percentage of platelet and leukocyte in modified (A-PRF) membrane was found to be higher in uncontrolled type-2 diabetic patients. Female subjects exhibited higher platelet and leukocyte concentration than males.